2015
DOI: 10.1108/ijopm-07-2013-0329
|View full text |Cite
|
Sign up to set email alerts
|

Partial and iterative Lean implementation: two case studies

Abstract: Purpose of this paper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 60 publications
1
92
0
7
Order By: Relevance
“…After careful consideration the research team identified two clusters, one in the north-west of Germany where three SMEs in the food manufacturing supply chain were selected and a further cluster of four SMEs in the south west of Germany where there was heavy manufacturing for the automotive and aerospace supply chain. Food manufacturing sector was selected to represent as perishable, low margin and high volume product (Bamford et al, 2015) in one side of the spectrome, whilst heavy automotive and aerospace manufacturing represents the opposite side of the spectrome. Each SME was initially contacted by the UK researchers to assess suitability for the study and then a visit to the companies was arranged.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After careful consideration the research team identified two clusters, one in the north-west of Germany where three SMEs in the food manufacturing supply chain were selected and a further cluster of four SMEs in the south west of Germany where there was heavy manufacturing for the automotive and aerospace supply chain. Food manufacturing sector was selected to represent as perishable, low margin and high volume product (Bamford et al, 2015) in one side of the spectrome, whilst heavy automotive and aerospace manufacturing represents the opposite side of the spectrome. Each SME was initially contacted by the UK researchers to assess suitability for the study and then a visit to the companies was arranged.…”
Section: Methodsmentioning
confidence: 99%
“…The goal of LSS, similar to Six Sigma, is to focus on low hanging fruits and eliminate waste factors known as defects by accomplishing a near perfect quality level through the systematic removal of causes of the defects (Dora and Gellynck, 2015;Choi et al, 2012). LSS benefits from both Six Sigma and Lean by incorporating a focus on cost, process cycle time, delivery value and efficiency from Lean and Kaizen and sustainable and incremental process improvement and profitability from Six Sigma (Bamford et al, 2015;Holmes et al, 2015;Worley and Doolen, 2015;Atmaca and Girenes, 2013;Sarkar et al, 2013;Womack and Jones, 2005). At an operational level within the manufacturing sector, the LSS model aims to clarify the process of identifying opportunities, as well as reduce variability and improve the quality of the manufacturing process (Holmes et al, 2015;Thomas et al, 2009).…”
Section: Lss In Manufacturing Smesmentioning
confidence: 99%
See 1 more Smart Citation
“…A careful review of the lean literature reveals a growing interest in the mechanisms through which lean practices affect firm performance and the extent of this effect (Secchi and Camuffo, 2016;Bamford et al, 2015;Arlbjørn and Freytag, 2013). This body of literature can be divided into three streams.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…De acordo com Bamford et al (2015), o processo de implementação da produção enxuta ocorre de forma interativa e pode resultar em implementações parciais. Considerando essa parcialidade na implementação, uma vez que o processo é longo e precisa de sistemas de feedback para o acompanhamento do progresso, ressalta-se a importância dos métodos que buscam avaliar o estágio de implementação da produção enxuta nas empresas.…”
Section: Introductionunclassified